METODOLOGI GROUNDED THEORY - Adibah, Ida Zahara (INSPIRASI (Jurnal Kajian dan Penelitian Pendidikan Islam), 2018)
ABSTRACTGrounded theory was first introduced by Glasser and Strauss in The Discovery of Grounded Theory (1967). The main purpose, first rationalizing the theory that is grounded, processed and developed by data processing activities during the research process takes place. According to Glaser and Strauus, this type of theory "bridges the gap between theoretical research and empirical research. The second objective is to formulate the logic and characteristics of grounded theory. Whereas the third is to legitimize qualitative research. Grounded theory is a systematic qualitative research procedure, in which the researcher is a theory that explains concepts, processes, actions, or interactions regarding a topic at a broad conceptual level. For that purpose, what is needed in the process towards theory is a planned and systematic procedure. Grounded theory is a general methodology for developing theory.Grounded theory is almost the same as other theories used in qualitative research. The data sources needed are the same, which includes interviews and field observations. The difference between this methodology and other qualitative methodologies lies in the development of theory. Researchers can achieve any theoretical goal when using grounded theory procedures. It's just that some grounded theory research tends to lead to the development of substantive theories. Grounded theory diperkenalkan pertama kali oleh  Glasser dan Strauss dalam The Discovery of Grounded Theory (1967). Tujuan utamanya, pertama merasionalisasikan teori yang digroundedkan ,diolah dan dikembangkan oleh aktivitas pengolahan data  selama proses penelitian berlangsung. Menurut Glaser dan Strauus ,teori jenis ini “menjembatani kesenjangan yang terjadi antara penelitian teoritis  dengan penelitian empiris. Tujuan kedua adalah merumuskan logika dan ciri khas dari grounded theory. Sedangkan ketiga adalah melegitimasi penelitian kualitatif. Grounded theory merupakan prosedur penelitian kualitatif yang sistematik, dimana peneliti suatu teori yang menerangkan konsep, proses, tindakan, atau interaksi mengenai suatu topic pada level konseptual yang luas. Untuk maksud itu, yang diperlukan dalam proses menuju teori itu adalah prosedur yang terencana dan teratur (sistematis). Grounded theory  adalah metodologi umum untuk mengembangkan teori. Grounded theory hampir sama  dengan teori-teori lain yang digunakan di dalam penelitian kualitatif. Sumber data yang diperlukan sama yakni meliputi wawancara dan observasi lapangan. Perbedaan metodologi ini dengan metodologi kualitatif lain terletak pada pengembangan teori. Para peneliti bisa mencapai tujuan teoritis apa saja ketika menggunakan prosedur grounded teory. Hanya saja sebagian penelitian grounded theory cenderung mengarah pada pengembangan teori substantive.